Horta escolar como estratégia de ensino para a educação ambiental formal - Kopeginski, Sandra Inês Reisdorfer (2023)
The objective of this research is to investigate the relationship between environmental education, food, and nutrition education at school through the development of the School Garden, here taken as an important pedagogical resource for the construction of an interdisciplinary teaching strategy. It is characterized as qualitative research as to the content analysis regarding the dynamic socio-environmental and educational research. This study asks if the School Garden as a pedagogical resource in environmental education meets the goal of making the correlation between food and environment resulting in changes in eating behavior and respect for the environment of the students. The current legislation and some theoreticians who research the theme are used as a basis, and the instrument for data collection is a bibliographic and documental survey and interviews with teachers from 1st to 5th grade of elementary schools, located in the area covered by the Association of Municipalities of the Western Region of Paraná (AMOP). The empirical data collected, transcribed, and analyzed allow us to highlight the School Garden as a teaching strategy in which the use of natural resources in and to produce food in a sustainable way enables the acquisition of healthy eating habits, through the understanding of what is consumerist behavior and unbalanced eating. The relevance of this study is justified by understanding the importance of the School Garden in the development of healthy eating mechanisms. It is noted that the incorporation of practical activities in the praxis is for the teacher an effective way to promote necessary changes in contemporary education and School Garden projects in the axis of environmental education print relevant challenges to transform teaching and offer the student varied ways to combine theoretical and practical content, allowing learning to occur in other spaces, outdoors, in direct contact with nature. We conclude that studies of this nature are relevant because they provide an opportunity to understand the relationship between healthy eating and a balanced environment.